Optimising the Polyphenolic Content and Antioxidant Activity of Green Rooibos (Aspalathus linearis) Using Beta-Cyclodextrin Assisted Extraction - Vhangani, Lusani Norah; Favre, Leonardo Cristian; Rolandelli, Guido; Van Wyk, Jessy; Buera, María del Pilar (2022)
Antioxidant activity associated with green rooibos infusions is attributed to the activity of polyphenols, particularly aspalathin and nothofagin. This study aimed to optimise β-cyclodextrin (β-CD)-assisted extraction of crude green rooibos (CGRE) via total polyphenolic content (TPC) and antioxidant activity assays. Response surface methodology (RSM) permitted optimisation of β-CD concentration (0–15 mM), temperature (40–90 °C) and time (15–60 min). Optimal extraction conditions were: 15 mM β-CD: 40 °C: 60 min with a desirability of 0.985 yielding TPC of 398.25 mg GAE·g−1, metal chelation (MTC) of 93%, 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging of 1689.7 µmol TE·g−1, ferric reducing antioxidant power (FRAP) of 2097.53 µmol AAE·g−1 and oxygen radical absorbance capacity (ORAC) of 11,162.82 TE·g−1. Aspalathin, hyperoside and orientin were the major flavonoids, with quercetin, luteolin and chrysoeriol detected in trace quantities. Differences (p < 0.05) between aqueous and β-CD assisted CGRE was only observed for aspalathin reporting the highest content of 172.25 mg·g−1 of dry matter for extracts produced at optimal extraction conditions. Positive, strong correlations between TPC and antioxidant assays were observed and exhibited regression coefficient (R2) between 0.929–0.978 at p < 0.001. These results demonstrated the capacity of β-CD in increasing polyphenol content of green rooibos.